Psychological consequences in women victims of partner violence - Colque Casas, José Luis (2020)
The study aimed to determine the psychological consequences of women victims of violence by their partner. The study design was non-experimental, cross-sectional in descriptive scope. We worked with a sample of 108 women who denounced their partners for violence in the constitutional province of Callao during the years 2018 and 2019, whose sample consisted of 108 women victims of violence by their partner. Derogatis SCL-90 R District Symptoms Checklist was used, which identifies psychological symptoms using nine dimensions and three global indexes of distress. Among the results regarding psychological suffering in victims of abuse by their partners: this is superior to that of outpatient psychiatric patients. On the other hand, regarding the dimensions of primary symptoms, the following stand out: depression (X = 1.81), obsession - compulsion (X = 1.74), anxiety (X = 1.70) and somatization ( X = 1.69). While the total global indexes: women victims of abuse have an average of 56 positive symptoms. And it was concluded that the psychological symptoms presented by women victims of violence by their partners are above the outpatient psychiatric population (52.03), which is supported by the average number of positive symptoms found (56 ). The dimensions that stand out in these women victims by their partner are: depression, obsession - compulsion, anxiety and somatization.